Correction: A microporous Cu-MOF with optimized open metal sites and pore spaces for high gas storage and active chemical fixation of CO2. Issue 51 (8th June 2018) - Gao, Chao-Ying; Tian, Hong-Rui; Ai, Jing; Li, Lei-Jiao; Dang, Song; Lan, Ya-Qian; Sun, Zhong-Ming
Abstract : Correction for 'A microporous Cu-MOF with optimized open metal sites and pore spaces for high gas storage and active chemical fixation of CO2 ' by Chao-Ying Gao et al., Chem. Commun., 2016, 52, 11147–11150.